2015
DOI: 10.1038/srep14715
|View full text |Cite
|
Sign up to set email alerts
|

Natural small molecule FMHM inhibits lipopolysaccharide-induced inflammatory response by promoting TRAF6 degradation via K48-linked polyubiquitination

Abstract: TNF receptor-associated factor 6 (TRAF6) is a key hub protein involved in Toll-like receptor-dependent inflammatory signaling pathway, and it recruits additional proteins to form multiprotein complexes capable of activating downstream NF-κB inflammatory signaling pathway. Ubiquitin-proteasome system (UPS) plays a crucial role in various protein degradations, such as TRAF6, leading to inhibitory effects on inflammatory response and immunologic function. However, whether ubiquitination-dependent TRAF6 degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Because K48‐linked polyubiquitin chains often promote proteasome‐mediated degradation (Zeng et al ., 2015; Zhang et al ., 2016), BGC823 and MGC803 cells were treated with the proteasome inhibitor bortezomib along with TRAIL. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because K48‐linked polyubiquitin chains often promote proteasome‐mediated degradation (Zeng et al ., 2015; Zhang et al ., 2016), BGC823 and MGC803 cells were treated with the proteasome inhibitor bortezomib along with TRAIL. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This experiment revealed that isoacteoside can significantly protect mice and that it is more effective than DEX, a drug used clinically to treat inflammation (Figure B). A efficacy of a higher dose of DEX (7 or 10 mg·kg −1 ) was found to be greater in mice with LPS‐induced endotoxaemia (Rocksen et al , ; Zeng et al , ; Qin et al , ). However, in terms of side effects, only those observed with the lower dosage of DEX (5 mg·kg −1 ) are reasonable and still meet the clinical requirements (Cicarelli et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone (DEX, 5 mg·kg −1 , i.p.) was used as positive control because it has a superior anti‐inflammatory effect (Zeng et al , ; Qin et al , ) and has been used in a clinical study to treat an endotoxic shock (Zhang et al , ). The survival rate was monitored continuously for 132 h. After 132 h, the remaining mice were killed by cervical dislocation under ether anaesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…The sequences of the PCR primers for each gene are described in Supplementary Table 2. The relative transcriptional level of target genes was calculated by the 2 − ΔΔCT method with GAPDH as a normalizing gene ( Zeng et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%